Baseline investigation on enzyme induced calcium phosphate precipitation for solidification of sand - Gowthaman, Sivakumar; Yamamoto, Moeka; Chen, Meiqi; Nakashima, Kazunori; Kawasaki, Satoru (Frontiers in Built Environment, 2023)
Bio-cementation processes [namely, microbial induced carbonate precipitation (MICP) and enzyme induced carbonate precipitation (EICP)] have recently become promising techniques for solidifying loose sands. However, these methods release gaseous ammonia to the atmosphere, which is not desirable for real-scale applications. This study aims to propose an enzyme induced calcium phosphate precipitation (EICPP) method as a sustainable direction for the solidification of sand. Precipitation of calcium phosphate compound (CPC) was driven through pH-dependent mechanism regulated by enzymatic hydrolysis of urea. The baseline study was designed to consist of a series of precipitation tests and sand column tests, evaluating the influence of various recipes of cementation media (CM) on treatment efficiency. The observations showed that the content of urea had an important role in proposed EICPP treatment, which determined the extent of the pH increase. This increase had a great influence on (i) utilization of soluble calcium, (ii) precipitation content of calcium phosphate, and (iii) the morphology of the precipitates. Results of sand column test suggested that injecting CM that consisted of acid-dissolved bone meal, urea and urease enzyme could result in the deposition of insoluble CPC that enabled the solidification of sand particles. The precipitation quantity was found to increase with the increase in urea content; however, the treatment media with high urea content resulted amorphous-like crystals. The plate-like crystals were evidenced in CM with [Ca]/[urea] molar ratio between 1.5 – 2.0. X-ray Diffraction (XRD) analysis revealed that irrespective of the urea contents, the formed crystals were identified as brushite. Since the final pH of proposed EICPP method could be controllable within acidic-neutral conditions, the emission of ammonia gas would be eliminated.